2020
DOI: 10.1111/1440-1681.13232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of imidazoline‐1 receptor agonists on renal dysfunction in rats associated with chronic, sequential fructose and ethanol administration

Abstract: Insulin resistance and chronic alcoholism are risk factors for renal dysfunction. This study investigated the therapeutic effects of two imidazoline‐1 receptor (I1R) agonists on renal dysfunction in rats after chronic, sequential fructose and ethanol administration. Daily drinking water was supplemented with fructose (10%, w/v) for 12 weeks and then with ethanol (20%, v/v) for another 8 weeks. Rats were treated with rilmenidine and clonidine in the last two weeks of the study. Blood glucose and serum insulin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…We showed previously and in the current study that feeding Swiss albino mice with HFrHFD for 16 weeks induces an early stage of IR characterized by slightly reduced or normal body weight, normo- or slight hyperglycemia, and profound hyperinsulinemia [13, 14]. Both fructose and saturated fats used in this type of diet contribute to the IR state by promoting the degradation of the IRS-1 and downregulation of the insulin receptors [21, 22]. In addition, saturated fats through their effect on FFAR1 can mediate hyperinsulinemia, the main characteristic feature of this model [23].…”
Section: Discussionmentioning
confidence: 89%
“…We showed previously and in the current study that feeding Swiss albino mice with HFrHFD for 16 weeks induces an early stage of IR characterized by slightly reduced or normal body weight, normo- or slight hyperglycemia, and profound hyperinsulinemia [13, 14]. Both fructose and saturated fats used in this type of diet contribute to the IR state by promoting the degradation of the IRS-1 and downregulation of the insulin receptors [21, 22]. In addition, saturated fats through their effect on FFAR1 can mediate hyperinsulinemia, the main characteristic feature of this model [23].…”
Section: Discussionmentioning
confidence: 89%
“…3 Furthermore, it has been confirmed that chronic kidney disease patients account for 10% of the world's total population. 4,5 As such, a new method for cure of renal fibrosis is of great significance. HGF) contains an α-chain and a β-chain.…”
Section: Introductionmentioning
confidence: 99%